The effects of foliar nutrition containing various macro and microelements on the growth and development of young grafted walnut (Juglans regia L.) plants - Solar, A. (International Journal of Horticultural Science, 2003)
The Stopgril liquido (S), a foliar fertilizer containing nitrogen, calcium and magnesium was used to improve the spring and the summer growth of grafted walnut plants in the second year of cultivation in the nursery. To accomplish early termination of vegetative growth and good lignification, the composed mineral fertilizer Hascon M 10 AD (H) containing phosphorous, potassium and microelements B, Mn and Mo was applied on the same plants. Four treatments (S, H, SH, C) were applied three times in a growing season. Their effects on the height and the basal diameter of the plants in the nursery depended on the starting height of the plants and the time of application. During the first growth period in the orchard, the number of developed buds on the plant, the circumference of the plants and their height were influenced by the treatment in the previous year in the nursery. According to the results obtained through the investigation, three applications of Stopgril + Hascon in the nursery per year can be recommended in order to obtain high enough and well lignified two-year-old grafted walnut plants.